STRATEGI PENGEMBANGAN PASAR TRADISIONAL BERBASIS KEARIFAN LOKAL UNTUK MENGENTASKAN KEMISKINAN DI BALI - I Putu Gde Sukaatmadja; Ni Nyoman Kerti Yasa; Henny Rahyuda; I G. A. Ngr Jaya Widagda (Faculty of Economics and Business Udayana University, 2014)
The aim of this research is to formulate development strategy of traditional market based on local wisdom to alleviate poverty. This study was taken in Bali Province. The sample determined by nonproportionate random sampling. The samples were 18 heads of traditional market in Bali. The data processed by SWOT analysis with Internal External Matrix (IE Matrix). The result shows that the opportunities consists of income percapita, inflation growth, traditional market revitalisation policy, stabilisation, social awareness, communityappreciation, communiy taste changes, and adoption of information technology, the threats were the existenceof modern market and population growth. The future strengths are product diversify, local productdifferentiation, product quality, merchandise layout, price flexibility, and strategy location. Whereas, theweaknesses are parking area availabilitry, transaction process, promotion, cooperation with tourism industry,market cleanliness, public facilitity availability, and consumer services. Based on the SWOT analysis, businessposition of traditional market are in cell-1 which is further become the basis for development strategy, i.e.“Growth and Maintenance Strategy”